A5.27 Ro52 Expression is a Prognostic Factor for Survival in B Cell Lymphoma. (25th February 2013) - Brauner, Susanna; Zhou, Wei; Backlin, Carin; Green, Tina M; Young, Ken He; Löfström, Björn; Lundberg, Ingrid; Pedersen, Lars Møller; Møller, Michael Boe; Sundström, Christer; Enblad, Gunilla; Baecklund, Eva; et al.
Abstract : Background and Objectives: The risk for lymphoma is increased in many rheumatic conditions. Diffuse Large B-cell Lymphoma (DLBCL) is a common, yet heterogeneous lymphoma subtype and good prognostic biomarkers are warranted. We have previously shown that the rheumatic autoantigen Ro52 is expressed predominantly in leukocytes and that over expression affects lymphocyte proliferation. Further, the Ro52 ( Trim21 ) gene maps to a tumour suppressor locus. We therefore hypothesised that Ro52 expression might be used as a prognostic marker for lymphoma. Materials and Methods: Proliferation of in vitro stimulated lymphocytes was determined by thymidine incorporation and cell cycle analysis and compared to Ro52 mRNA levels. Three cohorts of patients with DLBCL were investigated for Ro52 expression by immunohistochemistry using monoclonal Ro52 antibodies. The first cohort consisted of patients with rheumatic disease treated with cytostatic drugs only (n = 43). The two others were non-rheumatic patients treated with anthracycline-based (CHOP) therapy alone (n = 74), and with the addition of Rituximab (n = 196). Results: A robust inverse correlation between Ro52 expression levels and cellular proliferation was observed (r 2 = 0.50, p < 0.0001). Confirming this biological phenomenon, low expression of Ro52 in lymphoma tissue was significantly correlated to overall survival (p < 0.0001), as well as progression-free survival (p < 0.0001) in patients with DLBCL treated with CHOP therapy alone. This was further confirmed in the Rituximab-CHOP treated cohort, with a significantly lower overall survival (p < 0.0001) and progression-free survival (p = 0.0005). The association was independent of Ann Arbor classification and DLBCL subtype, emphasising that Ro52 expression is a parameter of added value in lymphoma investigations to understand the patient prognosis. Conclusions: Our data demonstrate that low Ro52 expression is associated with more aggressive lymphomas. Further, our data functionally link low Ro52 expression with increased cellular proliferation. Ro52 may thus constitute a novel biologically relevant biomarker predicting patient survival in lymphoma.